1971
DOI: 10.1111/j.1469-8137.1971.tb04595.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐pollination Phenomena in Orchid Flowers

Abstract: SUMMARYNAA, in concentrations exceeding o.oi /Ug/flower, initiates post-pollination phenomena in Cymbidium (Orchidaceae) flowers similar to those brought on by pollination. These include stigmatic closure, swelling and loss of curvature of the column, wilting of the perianth, deformation of the calli, and anthocyanin production. Applications of relatively high concentrations of GA3 induce post-pollination effects which, except for anthocyanin production, are less intense than those brought about by auxin. Kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Auxin is reported to play important roles in orchid development ( Arditti et al, 1971 ; Tsavkelova et al, 2007 ; Novak and Whitehouse, 2013 ; Novak et al, 2014 ). However, it is not clear how auxin responses are regulated to coordinate specialized orchid developmental programs.…”
Section: Discussionmentioning
confidence: 99%
“…Auxin is reported to play important roles in orchid development ( Arditti et al, 1971 ; Tsavkelova et al, 2007 ; Novak and Whitehouse, 2013 ; Novak et al, 2014 ). However, it is not clear how auxin responses are regulated to coordinate specialized orchid developmental programs.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors also had no effect, suggesting absence of a role of auxin in Iris tepal senescence. Auxins promoted senescence in carnation petals (Sacalis ) and in tepals of orchids such as Cymbidium (Arditti et al ). These flowers have ethylene‐regulated petal/tepal senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that application of NAA to the orchid stigmatic surface mimics the floral senescence response triggered by pollination. [26][27][28] Auxin initiates rapid changes, including elongation of ovary epidermal cells to form trichomes, an increase in ovary diameter, and, depending on the species, initiation of ovule development or maturation of partially developed ovules. 13,14,29 Most of these changes are mediated through auxin-stimulated ethylene production.…”
mentioning
confidence: 99%